Change from Above and Resistance to Change in the Early Prescriptive Pronouncing Dictionaries of English - Trapateau, Nicolas; Duchet, Jean-Louis (Studia Anglica Posnaniensia, 2019)
Walker’s prescription is a complex combination of both promotion of, and resistance to pressures from above according to criteria that reflect the ideals of the upper middle class.